Cereal production and technology adoption in Ethiopia - Yu, Bingxin; Nin-Pratt, Alejandro; Funes, José; Gemessa, Sinafikeh Asrat (International Food Policy Research Institute, 2011)
The Ethiopian government has been promoting a package-driven extension that combines credit, fertilizers, improved seeds, and better management practices. This approach has reached almost all farming communities, representing about 2 percent of agricultural gross domestic product in recent years. This paper is the first to look at the extent and determinants of the adoption of the fertilizer-seed technology package promoted in Ethiopia using nationally representative data from the Central Statistical Agency of Ethiopia. We estimate a double hurdle model of fertilizer use for four major cereal crops: barley, maize, teff, and wheat. Since maize is the only crop that exhibits considerable adoption of improved seed, we estimate a similar model for the adoption of improved seed in maize production. We find that access to fertilizer and seed is related to access to extension services and that production specialization together with wealth play a major role in explaining crop area under fertilizer and improved seed. One of the most important factors behind the limited adoption of the technological package is the inefficiency in the use of inputs, which implies that changes are needed in the seed and fertilizer systems and in the priorities of the extension service to promote more efficient use of inputs and to accommodate risks associated with agricultural production, especially among small and poor households.